2021
DOI: 10.1080/23744235.2021.1940271
|View full text |Cite
|
Sign up to set email alerts
|

Adjunctive treatment with high-titre convalescent plasma in severely and critically ill COVID-19 patients – a safe but futile intervention. A comparative cohort study

Abstract: Background Convalescent plasma (CP) containing antibodies derived from coronavirus disease 2019 (COVID-19) survivors has been proposed as a promising therapeutic option for severe COVID-19. Methods In our intensive care unit (ICU), 55 patients (46 male, median age 61 years) with PCR-confirmed COVID-19 (35 = 63.6% on mechanical ventilation, 7 = 14.5% on high-flow nasal oxygen, 12 = 20% on non-invasive ventilation, 1 = 1.8% without respiratory support) were treated with h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 45 publications
0
13
0
1
Order By: Relevance
“…A total of 4728 records were identified from databases, websites and citation searching. There were 47 studies 16‐62 fulfilled the inclusion criteria and were used for the systematic review and meta‐analysis (Figure 1). Of 47 included studies, 21 were clinical trials 16‐33,60‐62 and 26 were observational studies 34‐59 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 4728 records were identified from databases, websites and citation searching. There were 47 studies 16‐62 fulfilled the inclusion criteria and were used for the systematic review and meta‐analysis (Figure 1). Of 47 included studies, 21 were clinical trials 16‐33,60‐62 and 26 were observational studies 34‐59 .…”
Section: Resultsmentioning
confidence: 99%
“…Of 47 included studies, 21 were clinical trials 16‐33,60‐62 and 26 were observational studies 34‐59 . Among clinical trials, there were 18 studies published in peer‐reviewed journals 16‐33 while the other three were preprints 60‐62 . Among clinical trials, there were 14 studies used the randomization process 17‐20,23,25,26,28,30,31,33,60‐62 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Einen interessanten Ansatz stellt die Behandlung von kritisch kranken COVID-19 Patientinnen und Patienten mit Rekonvaleszentenplasma dar. Die Autoren haben ihn bei 55 Patientinnen und Patienten auf ihrer Intensivstation angewendet, jedoch trotz eines hervorragenden Sicherheitsprofils (keine einzige nachgewiesene „adverse reaction“) keinen positiven Effekt auf das Überleben gesehen [ 23 ]. Dies deckt sich mit internationalen Publikationen: In einer indischen Studie mit über 230 plasmabehandelten, moderat (Horowitz-Index 200–300 mmHg) an COVID-19 erkrankten Patientinnen und Patienten konnte im Vergleich zum Placebo kein Effekt auf den Progress zu einer schwereren Erkrankung oder auf das Überleben gezeigt werden [ 24 ].…”
Section: Medikamentöse Therapieunclassified
“…It has been well‐established that antibody‐based passive immunotherapy is an effective approach to combat virus infection. 1 Recent reports have demonstrated that the administration of convalescent plasma containing neutralizing antibodies can improve the clinical status of some critically ill patients 2 , 3 , 4 , 5 ; however, the outcomes of passive plasma therapy are unpredictable, and the wide‐spread clinical use of plasma therapy is unrealistic. Therefore, it is important to develop neutralizing antibodies that can be administered to enhance the prevention and treatment of COVID‐19.…”
Section: Introductionmentioning
confidence: 99%